International Standards and Domestic Experience of Population Income Measurement: Russia and Regions - S. G. Bychkova (Управление)
The article is devoted to the consideration of the information base for studying the incomes of the population, the standards used in international and domestic statistical practice, studying the main indicators of welfare and income of the population used in the Russian Federation, estimating the structure of incomes in the regions of the Russian Federation, and analyzing their differences in the territorial entities of the country. The article studies the relationship between the main indicators of income and welfare in 2011-2016.